PVTx properties of binary R1234ze(E)/R600a system. (August 2017) - Cao, Rui; Qi, Yingxia; Chen, Rishuai
Highlights: PVTx experimental data of (R1234ze+R600a) mixtures at six mass fractions. Compositions of mixtures studied were from 65 to 90 mass% of R1234ze(E). Virial equations of gas phase state. Abstract: The gaseous pVTx properties of trans -1, 3, 3, 3-tetrafluoropropene (R1234ze(E)) + 2-methylpropane (R600a) mixtures were measured in temperatures from 280.15 to 330.15 K and corresponding pressures from 138 to 930 kPa and the compositions of R1234ze(E) from 0.65 to 0.90 mass fraction using the Burnett isothermal expansion method. The uncertainties of experimental device was estimated to be within ±10 mK for temperature, ±10 kPa for pressure, and ±0.001 mass fraction for composition and 0.5% for density. Meanwhile, the density and gas virial equation of state of the mixed refrigerants were fitted on the basis of the experimental pVTx property data. It provided thermophysical parameters for the further research on the performance of the mixed refrigerants as new alternative refrigerants.